(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Although modern anaesthesiology has made great progress in the last decades and spinal anaesthesia is popular for its effectiveness, Post Dural Puncture Headache (PDPH) is a significant and well known complication of spinal anaesthesia that may be incapacitating for patients. A few decades ago less refined and thicker spinal needles were being used and the incidence of PDPH was high. But within the last 15 years more refined and thinner needles have been used and the incidence of PDPH is grossly reduced. Objective: To compare the incidence and severity of post dural puncture headache using 25 G Quincke and 27 G Quincke needle during spinal anaesthesia in case of caesarean section. Materials and Methods: This randomized prospective study was carried out in the Border Guard Hospital, Dhaka, during the period of January to July, 2015. Patients were selected randomly from the age group of 20-35 years having a pregnancy of at least 34 weeks gestation with a single uncompromised fetus and uncomplicated pregnancy. Patients with a history of migraine, convulsion, cerebrovascular accident, Pre-eclampsia, eclampsia, spinal deformity, coagulopathy or previous neurological disease were excluded. They were randomly allocated into two groups. Each group consisting of 50 patients. Data was collected by interviewing and observation results. Data were processed and analyzed by using statistical test. Results: There was no statistically significant difference found in age, height, weight and ASA status between two groups. 27G Quincke needle had significantly higher failure rate of successful lumber puncture in first attempt than the 25G Quincke needle (20% vs 6%, P<0.05). There was no difference difference regarding the incidence of intraoperative complications between two groups. The overall incidence of PDPH was 2(4%) in group A and 12 (24%) in group B (P<0.05). Decreased severity of headache was noted in the 27G group Quincke needle. There was no difference regarding the duration of headache in between two groups. Conclusion: This study suggests that the risk of PDPH was much lower in 27G Quincke needle as compared to 25G Quincke needle though it had a higher failure rate of successful lumber puncture in first attempt. For spinal anaesthesia 27G Quincke needle should be used. Journal of Armed Forces Medical College Bangladesh Vol.12(1) 2016: 17-21